동기관리 프로그램이 학업 및 진로 스트레스를 지닌 여대생의 스트레스 반응, 자기효능감 및 주관적 웰빙에 미치는 영향 - 장지혜(Ji-Hye Jang); 김정호(Jung-Ho Kim); 김미리혜(Mirihae Kim) (Seuteureseu yeon-gu (Online), 2017)
본 연구는 동기관리 프로그램이 학업 및 진로 스트레스를 지닌 여대생의 스트레스 반응(신체화, 우울,분노), 자기효능감, 주관적 웰빙에 미치는 효과를 검증했다. 서울 소재 대학에 재학 중인 여대생 25명을대상으로 처치집단에 12명, 통제집단에 13명을 할당했다. 처치집단은 주 1회 80분씩, 총 6회기의 동기관리 프로그램에 참여했다. 분석 결과, 처치집단이 통제집단에 비해 사전검사보다 사후검사에서 스트레스 반응, 신체화, 우울, 분노, 부정정서가 더 감소했고, 삶의 만족, 긍정정서가 더 증가했으며, 이러한변화는 통계적으로 유의했다. 그러나 자기효능감, 삶의 만족예상은 집단 간 사전-사후의 차이가 유의하지 않았다. 끝으로 본 연구의 의의와 한계점, 후속 연구를 위한 제안에 대하여 논의하였다. Background: This study examined the effects of the Motivation Management Program on stressresponse (somatization, depression, and anger), self-efficacy and subjective well-being among femaleuniversity students with academic and career stress. Methods: The participants were assigned to either a treatment group (N=12) or a control group(N=13). The Motivation Management Program treatment group was administered 6 sessions (80minutes each, once a week). Results: The Stress Response, Somatization, Depression, Anger and Negative Affect scores in thetreatment group decreased significantly compared with those in the control group, while theSatisfaction with Life and Positive Affect scores in treatment group increased significantly incomparison with those in the control group. No significant pre-post differences were found betweengroups in Self-Efficacy and Life Satisfaction Expectancy scores. Conclusions: The findings suggest that the motivation management program can help femaleUniversity students reduce the stress response (somatization, depression, and anger) and improve thesubjective well-being. KCI Citation Count: 1